POLA PENDIDIKAN AGAMA ISLAM PADA KELUARGA PETANI DI DESA WATU TOA KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Riyo Asmin Syaifin (Jurnal Risalah Addariyah STAI DDI Mangkoso, 2024)
This research discusses the pattern of Islamic religious education in farming families in Watu Toa Village, Marioriwawo District, Soppeng Regency. There are two main problems, 1) What is the pattern of Islamic religious education for children in farming families in Watu Toa Village, Marioriwawo District, Soppeng Regency? 2) What are the supporting and inhibiting factors for farming families in instilling Islamic religious education in Watu Toa Village, Marioriwawo District, Soppeng Regency? In this research, the author used a qualitative descriptive research type with a descriptive approach. The data sources used are primary and secondary. Data collection uses observation, interviews, and documentation. With research instruments using notebooks, pens, and cameras. The data analysis processing techniques used are data reduction, data display or data presentation, or concluding. The results of this research show that there are three patterns of Islamic religious education for children in farming families in Watu Toa Village, Marioriwawo District, Soppeng Regency, namely: habituation pattern, example pattern, and advice-giving pattern. Supporting factors in instilling Islamic religious education in Watu Toa village, Liliriaja subdistrict, Soppeng district are the influence of a conducive environment and parental awareness of the importance of education. And that the inhibiting factors in instilling Islamic religious education in Watu Toa Village, Liliriaja District, Soppeng Regency are busy parents, and children's awareness is still lacking regarding the importance of Islamic religious education. And the lack of parental knowledge about the Islamic religion.